1998
DOI: 10.1111/j.1572-0241.1998.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective case-cohort study of intestinal colonization with enterococci that produce extracellular superoxide and the risk for colorectal adenomas or cancer

Abstract: Significant associations were found for those with large adenomas or cancer (but not small adenomas), with age, and with foods enriched for vitamin A, vitamin E, and beta-carotene. An association between colonization with O2*--producing enterococci and colorectal adenomas or cancer, however, could not be ascertained, possibly because intestinal enterococcal flora changes over time, leaving a potentially cohesive hypothesis of colon cancer and risk factors as yet unanswered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Enterococci are the only intestinal bacteria known to produce extracellular superoxide (Huycke et al ., 1996; Winters et al ., 1998). Although the majority of aerotolerant prokaryotic organisms ordinarily produce small amounts of superoxide, this free radical production is located in the cytoplasm or periplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterococci are the only intestinal bacteria known to produce extracellular superoxide (Huycke et al ., 1996; Winters et al ., 1998). Although the majority of aerotolerant prokaryotic organisms ordinarily produce small amounts of superoxide, this free radical production is located in the cytoplasm or periplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Electroporation of E. faecalis with purified plasmid DNA was performed as described previously (Shepard and Gilmore, 1995). Oligonucleotides were synthesized and polymerase chain reaction (PCR) amplification performed as reported previously (Winters et al ., 1998). Chromosomal DNA flanking Tn 917 sequences was amplified by inverse PCR (Triglia et al ., 1988).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A large clinical study showed no association between colonization of the gut with E. faecalis and colorectal adenomas or cancer. 25 Interestingly, in a carefully designed study analyzing the bacterial flora in feces, patients suffering from colorectal cancer had higher populations of E. faecalis. 26 Whether this finding points to a potential cause or to a consequence of the disease is currently not clear.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is further underscored by the finding that E. faecalis fecal carriage was increased in CRC patients, whereas the number of butyrate producing bacteria was decreased (Balamurugan et al, 2008). However, no clinical evidence has been presented that associates superoxide producing enterococci with adenomas or CRC (Winters et al, 1998). This clearly indicates that, although the in vitro data and animal studies strongly suggest that oxygen radicals from bacterial origin could play an important role in CRC initiation or progression, the clinical impact of these findings remains to be properly examined in well-designed clinical studies (Huycke & Gaskins, 2004).…”
Section: Metabolite-induced Dna Damagementioning
confidence: 99%